A formação docente e seus reflexos no cotidiano da prática pedagógica ribeirinha - SOUZA, Raquel Cardoso de (2024)
For the preparation of this memorial, a serious and sincere commitment was necessary in relation to my life trajectory. This is emphasized in my memoirs, which I recalled was a necessary duty so that it could gain form to support its construction. In it I emphasize the autobiography of a teacher who seeks through the teaching profession to find the concrete way to contribute to an education that is really correct, turning to the importance of the PARFOR program for continuing education. The reader will note that the first chapter gives a retrospective of the events that were important in the educational context of children reaching adulthood and the processes that led me to enter the university educational process. By virtue of this direction, the second chapter aims to emphasize my teaching and the reason why I became a teacher, highlighting the processes that I had to go through in order to continue walking on this educational path. In turn, the third chapter, makes an approach to teacher training and its benefits that were of paramount importance to my professional performance. In the fourth and last chapter, I try to make a relation of what I learned in academic teaching without losing sight of the analysis of the pedagogical practice riverside and its daily life.